Spontaneous shaker rat mutant - a new model for X-linked tremor/ataxia - Karla P. Figueroa; Sharan Paul; Tito Calì; Raffaele Lopreiato; Sukanya Karan; Martina Frizzarin; Darren Ames; Ginevra Zanni; Marisa Brini; Warunee Dansithong; Brett Milash; Daniel R. Scoles; et al. (The Company of Biologists, 2016)
The shaker rat is an X-linked recessive spontaneous model of progressive Purkinje cell (PC) degeneration exhibiting a shaking ataxia and wide stance. Generation of Wistar Furth (WF)/Brown Norwegian (BN) F1 hybrids and genetic mapping of F2 sib-sib offspring using polymorphic markers narrowed the candidate gene region to 26 Mbp denoted by the last recombinant genetic marker DXRat21 at 133 Mbp to qter (the end of the long arm). In the WF background, the shaker mutation has complete penetrance, results in a stereotypic phenotype and there is a narrow window for age of disease onset; by contrast, the F2 hybrid phenotype was more varied, with a later age of onset and likely non-penetrance of the mutation. By deep RNA-sequencing, five variants were found in the candidate region; four were novel without known annotation. One of the variants caused an arginine (R) to cysteine (C) change at codon 35 of the ATPase, Ca2+ transporting, plasma membrane 3 (Atp2b3) gene encoding PMCA3 that has high expression in the cerebellum. The variant was well supported by hundreds of overlapping reads, and was found in 100% of all affected replicas and 0% of the wild-type (WT) replicas. The mutation segregated with disease in all affected animals and the amino acid change was found in an evolutionarily conserved region of PMCA3. Despite strong genetic evidence for pathogenicity, in vitro analyses of PMCA3R35C function did not show any differences to WT PMCA3. Because Atp2b3 mutation leads to congenital ataxia in humans, the identified Atp2b3 missense change in the shaker rat presents a good candidate for the shaker rat phenotype based on genetic criteria, but cannot yet be considered a definite pathogenic variant owing to lack of functional changes.